Bendy : dreams come to life - Kress, Adrienne; Hastings, Chris, 1983- (Bendy and the ink machine., 2024)
Seventeen-year-old Buddy is trying to escape the Lower East Side slums of New York City. He wants to become an artist, a dream he's sure will never be realized. But when a delivery job puts him face-to-face with Mister Joey Drew, eccentric owner of an animation studio, Buddy is taken on as an apprentice. But not everything at the studio is as picture-perfect as it seems...something is going bump in the night and leaving behind trails of thick, dark ink. While the studio works toward a deadline, Buddy and Dot the writing intern team up to find out what is tormenting the studio after hours, even though the trail may lead back to Mister Drew himself...